MODEL PEMBELAJARAN IPA TERINTEGRASI PBL, TaRL, DAN CASEL: STUDI KASUS KONTEKSTUAL DI SEKOLAH DASAR - Noer Cahya Anggraeni, Devi; Afandi, Muhamad; Jupriyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to investigate the effect of integrating Problem-Based Learning (PBL), Teaching at the Right Level (TaRL), and social-emotional competence (CASEL) in Science in elementary School. Used a qualitative approach as well as a case study, combining a literature review of 20 papers related to PBL, TaRL, and CASEL, as well as a case study involving 27 fifth-grade students at Gedawang 01 Elementary School. thematic literature review of 20 relevant studies was performed to explore the implementation of these three learning models and their effects on student engagement, academic achievement in science, and the development of social-emotional competencies. Data were collected through observations, in-depth interviews with teachers and students, and field notes documenting the classroom dynamics. The data were analyzed using thematic qualitative analysis to identify patterns in student engagement, emotional regulation, and the development of social skills. The results indicate that the integration of PBL, TaRL, and CASEL significantly enhances students' active participation, fosters a deeper understanding of scientific concepts, and improves their social-emotional skills, such as collaboration and conflict resolution. This study contributes to educational theory by demonstrating the value of an integrated learning approach that simultaneously enhances academic performance and social-emotional growth, crucial for the demands of 21st-century education This research provides practical implications for educators to implement a holistic approach in learning at the elementary school level.